2011
DOI: 10.1007/s00412-011-0320-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cytological characterization of repetitive DNA sequences from the centromeric heterochromatin of Sciara coprophila

Abstract: Sciara coprophila (Diptera, Nematocera) constitutes a classic model to analyze unusual chromosome behavior such as the somatic elimination of paternal X chromosomes, the elimination of the whole paternal, plus non-disjunction of the maternal X chromosome at male meiosis. The molecular organization of the heterochromatin in S. coprophila is mostly unknown except for the ribosomal DNA located in the X chromosome pericentromeric heterochromatin. The characterization of the centromeric regions, thus, is an essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…4 g). In addition, the “Sccr” ( Sciara centromere consensus sequence) repeat that hybridized to the centromeres of all Sciara chromosomes [ 23 ] mapped to 48–105 contigs (Table 2 , Fig. 4 g).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 g). In addition, the “Sccr” ( Sciara centromere consensus sequence) repeat that hybridized to the centromeres of all Sciara chromosomes [ 23 ] mapped to 48–105 contigs (Table 2 , Fig. 4 g).…”
Section: Resultsmentioning
confidence: 99%
“…The longest X-linked contig was 9.68 Mb (12 Mb). The set of haploid X-linked contigs contained those identified as X-linked using X-specific sequences above as well as contigs containing the F7 repeat sequence known to be on X, IV, and L [ 23 ] (Table 2 , Fig. 4 g, Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, an inverse correlation between predicted curvature and G + C content was found. The AT richness and the presence of AT runs are a fundamental feature of DNA curvature (Lorite et al , 2004; Palomeque & Lorite, 2008; Escribá et al ., 2011). Recently, Matyasek et al (2011) have reported a clear correlation between the existence of short and periodically phased T 4–6 and stDNA curvature.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to its molecular nature, the CE is located in the middle heterochromatic block of the pericentromeric region of the X chromosome of S. coprophila [Crouse, 1960a[Crouse, , b, 1977[Crouse, , 1979. Microdissection and microcloning of this region have already been performed [Escribá et al, 2011b] so that the molecular characterization of this region is now possible.…”
Section: Perspectivesmentioning
confidence: 99%
“…Recent molecular data challenged this contention. Escribá et al [2011b] microdissected and microcloned the pericentromeric region of the S. coprophila X chromosome, where the rDNA is located. They identified and characterized repeated DNA sequences, a RTE element and an AT-rich satellite, and as expected, rDNA clones were also recovered.…”
Section: Evolutionary Considerationsmentioning
confidence: 99%